Analysis of Air Flow, Air and Fuel Induction for Internal Combustion Engine - Arshad, Mohd Fitri; Ahmad, Muhammad Faris; Khalid, Amir; Ishak, Izuan Amin; Zainal Abidin, Shaiful Fadzil; Razali, Mohd Azahari (Journal of Automotive Powertrain and Transportation Technology, 2021)
In an internal combustion engine, performance, efficiency and emission formation depends on the formation of air-fuel mixture inside the engine cylinder. The fluid flow dynamics plays an important role for air-fuel mixture preparation to obtain the better engine combustion, performance and efficiency. This review article discuss the rotating flow (swirl and tumble) in premixed spark-ignition engine and its effect on turbulence generation and flame propagation. Rotating flow can substantially increase turbulence intensity for the duration of the combustion period. This review paper discusses the in-cylinder swirl and tumble flow that affects air induction during the combustion process in internal combustion engine. Alternatively, this study using computer simulation (Computational Fluid Dynamic, CFD) which offer the opportunity to carry out repetitive parameter studies. An integration-type flowmeter (IFM) also has been used which consists of ultrasonic flowmeter, that integrates the flowrate during the intake process, gives accurate measurements regardless of sampling time and frequency. Research parameter in this study was swirl and tumble that represents the fluid flow behavior occurred inside combustion chamber. Fuel injection and air mass also were the important parameters that have been discussed about in air induction process. The results obtain from the numerical analysis can be employed to examine the homogeneity of air-fuel mixture structure for better combustion process and engine performance.